Etnicidad vs. Aculturación - Barroso Cabrera, Rafael (Archaeopress, 2018)
A study of the political and archaeological controversies surrounding the Castilian Necropoleis of the V-VI Centuries AD and the Visigoth Settlement in the Iberian Peninsula. The author attempts to deconstruct the various controversies and presents fresh analysis based on the archaeological data and literary evidence.